Young Adult Cannabis, Alcohol, Nicotine, and Nonprescribed Pain Reliever Use in Washington State Before and During COVID-19 Pandemic - Fleming, Charles B.; Martinez, Griselda; Rhew, Isaac C.; Kilmer, Jason R.; Larimer, Mary E.; Guttmannova, Katarina (AJPM Focus, 2025)
The COVID-19 pandemic may have affected young adult use of cannabis and other drugs. Prior research provides information about these effects, but additional estimates are needed using data collected in a consistent manner across years and in an established legalized cannabis context. The authors assessed changes in substance use among young adults in Washington State during the pandemic relative to prior trends. Data were from young adults aged 18–25 years in 6 annual waves of the statewide Washington State Young Adult Health Survey (N=12,516). In analyses conducted in 2023 and 2024, the authors estimated trends in substance use from 2016 to 2019 and deflections from those trends in 2020 and 2021. Past-month cannabis use increased across years (annual percentage point change in 2016–2019 =1.6; 95% CI=0.6, 2.6), with little deflection from the prepandemic trend in 2020 or 2021. Prevalence of past-month alcohol use, heavy episodic drinking, cigarette use, and nonprescribed pain reliever use decreased across years (annual percentage point change range= −1.2, −0.5), with a further downward deflection from the prepandemic trend for cigarette use in 2020 (percentage point change= −3.8; 95% CI= −6.2, −1.4). Prevalence of simultaneous alcohol and cannabis use was stable across the study period. E-cigarette use increased before pandemic (annual percentage point change=1.8; 95% CI=1.2, 2.5) but fell below this trend in 2020 (percentage point change= −2.9; 95% CI= −4.8, −1.1) and 2021 (percentage point change= −3.2; 95% CI= −5.3, −1.0). For those aged <21 years compared with those aged ≥21 years, there was a downward deflection in cannabis use in 2020 (percentage point change=7.5; 95% CI=0.1, 14.9) and greater decrease in nonprescribed pain reliever use before pandemic (annual percentage point change=1.3; 95% CI=0.3, 2.3) followed by a relative increase in 2020 (percentage point change= −5.5; 95% CI= −11.6, 0.5). Sex differences in changes were not statistically significant, but females increased in most types of substance use relative to males across the study period. Prepandemic trends in cannabis and alcohol use continued through 2021, pointing to continuity in demand and supply, although the pandemic may have dampened cannabis use in 2020 for young adults aged <21 years. Decreases in nicotine use after 2019 may be partly due to restrictions on sales enacted in 2020 and warnings of COVID-19 risk linked to smoking and vaping. The findings point to the need for continued substance use prevention and treatment services during disruptive public health crises. •Prepandemic increases in young adult cannabis use prevalence continued through 2021.•In 2020, cannabis use diverged by age, with a small decrease among those aged <21 years.•Cannabis use increased more for females than for males across the study period.•Decreases in alcohol, cigarette, and pain reliever misuse continued through 2021.•Prepandemic increases in E-cigarette use leveled off during the pandemic.